Taxmann's corporate governance - Bansal, C. L. (New Delhi, 2005)
Corporate Governance involves the building of a set of relationships between the company, its Board, the management, the shareholders and other stockholders by putting in place a structure and a system through which the established goals of the company may be achieved. The corporate boards, as the apex governing organisations, are responsible for practising good governance. The quality of governance is reflected in many ways, inter alia, investors' willingness to invest, customer satisfaction or dissatisfaction, and whether company's equity is trading at prices well above or below the real economic value of the company. The recurrent corporate failures and corporate misconduct are a symptom that corporate governance mechanism has failed to come up to the expectations of various corporate constituencies. There is perceptible lack of public confidence in the honest functioning of corporate bodies. All these highlight the need to develop governance structures and tools that are capable of thwarting attempts to undermine norms of good governance.
Keywords: Law-Case studies